Cicada Killer, Giant Ground Hornet, Sphecius hogardii (Latreille) and Sphecius speciosus (Drury) (Insecta: Hymenoptera: Sphecidae) - Lionel A. Stange (EDIS, 2005)
Cicada killers, or giant ground hornets, are among the largest wasps in Florida (up to 40 mm in length). They are conspicuous insects, since the males are territorial and will butt or grapple with intruders including other males. There are 22 species of Sphecius Dahlbom in the world and all hunt cicadas as far as is known. Two of four Nearctic species of Sphecius occur in Florida. The females of the common Florida species, Sphecius speciosus (Drury), hunt Tibicen spp. cicadas and can dig 4-foot burrows in the ground with several branches and cells. The provisioning with cicadas is nearly specific to Sphecius in the family Sphecidae, but is known in a few other sphecids such as Liogorytes joergenseni (Brethes) from Argentina (Bohart and Stange 1976). This document is EENY295, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 2003. Revised January 10, 2005.